Uma carreira a serviço da guerra híbrida: a atuação do gen-ex Carlos Alberto Pinto Silva na campanha eleitoral militar (2015-2018) - Heck , Airlon Lucas (2023)
The historical phenomenon of political leadership of the hierarchical summits of the Armed Forces was evidenced in the recent military government (2019-2022) with the occupation of various state apparatus. To understand how this hegemony project came to power in the State government, we investigated the period prior to the 2018 federal elections, addressing how the barracks were targeted by psychological operations that fostered the military candidacy. In this context, we investigated the main role of General Carlos Alberto Pinto Silva (AMAN 1964 Class) through the publication of texts on the Defesanet website, in which he disseminated a particular vision of the concept of hybrid warfare, which was related to alleged activities undertaken by actors organized around the PT - Workers' Party to weaken the Armed Forces and take over the State power. Analyzing his career that began with the military dictatorship, his functions were in line with the Army's transformation processes, especially from the 1990s, when the Amazon became the center of gravity of the Force, and later in the 2000s when he joined the High Command and commanded several operations, promoting the need to adopt doctrines related to the "human terrain" of conflicts and the "new threats" projected in organized crime, especially on the country's border strip. His performance can be configured in the position of a military intellectual, collaborating to adopt the informational and human environment as the center of gravity of the Force, as well as fundamental to give credibility to the ideas of the "PT hybrid war" launched for the barracks in the context of the military electoral campaign. Thus, his participation in this process is part of the hybrid warfare activities undertaken by the military themselves to reach the State power. Therefore, we seek to demystify the military's performance through their tools of war, contributing to the historiographical debate on how the phenomenon of political leadership of the hierarchical summits of the Armed Forces occurs in the Immediate History of Brazil.